Association Between Sources of Social Support and Depression Among Nursing Students During the COVID-19 Pandemic - Kurniawan, Dedi; Fitriawan, Akbar Satria; Setyaningsih, Wiwit Ananda Wahyu; Wulandari, Apri Nur; Wijoyo, Eriyono Budi; Samutri, Erni; Suparmanto, Gatot; Achmad, Bayu Fandhi; Retnaningsih, Listyana Natalia; Sudiarti, Putri Eka (Nurse Media Journal of Nursing, 2024)
Background: Nursing students have a higher risk of depression due to their high academic burden, social isolation, pandemic loneliness, abrupt online learning, and financial difficulties during the COVID-19 pandemic lockdown. Although the disruption of social network patterns during the pandemic has been observed in previous studies, it is still not fully understood which source of social support is associated with depression among nursing students.Purpose: This study aimed to assess the correlations between sources of social support and depression among nursing students during the COVID-19 pandemic.Methods: An online cross-sectional study was conducted between May and September 2021. Nursing students (n=734) from seven universities across four provinces in Indonesia were recruited as participants using convenience sampling methods. Data were obtained through online questionnaires consisting of the Multidimensional Scale of Perceived Social Support (MSPSS) to assess social support and the Patient Health Questionnaire-9 (PHQ-9) to assess depression. Spearman-Rank correlation tests were used to examine the correlations between sources of social support and depression.   Results: Most of the nursing students (85.1%) were female, with a mean age of 19.94 years (SD=1.42). Many nursing students (n=313; 42.6%) experienced depression. Most of the students (n=465; 63.4%) perceived high family support, moderate friends (n=415; 56.5%) and significant others’ support (n=437; 59.5%). Of the three sources of social support (family, friends, and significant others), only family support had a significant inverse correlation with depression (Rho=-0.492, p<0.001).Conclusion: Family support had a significant inverse and moderate correlation with depression among nursing students during the COVID-19 pandemic. Our findings provided information to nursing educators to incorporate a strategy to maintain robust family support and regular depression assessments as part of the online learning curriculum. Therefore, it can be used to ameliorate depression among nursing students.